The Multifaceted Roles of Proline in Cell Behavior - Patriarca, Eduardo J.; Cermola, Federica; D’Aniello, Cristina; Fico, Annalisa; Guardiola, Ombretta; De Cesare, Dario; Minchiotti, Gabriella (Frontiers in Cell and Developmental Biology, 2021)
Herein, we review the multifaceted roles of proline in cell biology. This peculiar cyclic imino acid is: (i) A main precursor of extracellular collagens (the most abundant human proteins), antimicrobial peptides (involved in innate immunity), salivary proteins (astringency, teeth health) and cornifins (skin permeability); (ii) an energy source for pathogenic bacteria, protozoan parasites, and metastatic cancer cells, which engage in extracellular-protein degradation to invade their host; (iii) an antistress molecule (an osmolyte and chemical chaperone) helpful against various potential harms (UV radiation, drought/salinity, heavy metals, reactive oxygen species); (iv) a neural metabotoxin associated with schizophrenia; (v) a modulator of cell signaling pathways such as the amino acid stress response and extracellular signal-related kinase pathway; (vi) an epigenetic modifier able to promote DNA and histone hypermethylation; (vii) an inducer of proliferation of stem and tumor cells; and (viii) a modulator of cell morphology and migration/invasiveness. We highlight how proline metabolism impacts beneficial tissue regeneration, but also contributes to the progression of devastating pathologies such as fibrosis and metastatic cancer.